Sosialisasi Potensi Keberagaman dan Semangat Toleransi di Kelurahan Sulamu Kabupaten Kupang - Wula, Zainur; Arifin, Hadjrah; Nurani, Siti Syahida; Nggonggoek, Wellem; Bacotang, Bacotang (LP2M INSURI Ponorogo, 2021)
Multicultural diversity is a fact of life that exists in Indonesian people's lives which is the greatest gift of God should be maintained. By engaging the Bajo tribal community in the Sulamu village of Kupang, province East Nusa Tenggara, who share the livelihood in the village with people of different tribes and religions, this community service is methodologically carried out by doing socialization. The important objective of the socialization was to obtain the communal understanding within the Bajo ethnic community about the potential for diversity in order to realize the spirit of tolerance in Sulamu Village. By participating in the program, the Bajo people, who are all Muslims in religion, gain knowledge in increasing their insight into thinking and realizing harmonious relationships and mutual understanding in building peace, unity, integrity, and prosperity. Keberagaman multikultural merupakan fakta kehidupan yang ada dalam kehidupan masyarakat Indonesia dan merupakan anugerah Tuhan yang paling besar untuk dijaga. Dengan melibatkan masyarakat Suku Bajo di Desa Sulamu Kupang Provinsi Nusa Tenggara Timur yang hidup di desa tersebut dengan masyarakat beragam suku dan agama, program ini dilakukan dengan melakukan sosialisasi. Tujuan penting dari sosialisasi tersebut adalah untuk memperoleh pemahaman komunal dalam masyarakat etnis Bajo tentang potensi keragaman dalam rangka mewujudkan semangat toleransi di Desa Sulamu. Dengan mengikuti program tersebut, masyarakat Bajo yang beragama Islam memperoleh pengetahuan dalam meningkatkan wawasan berpikir dan mewujudkan hubungan yang harmonis dan saling pengertian dalam membangun perdamaian, persatuan, kesatuan, dan kesejahteraan.